Development and evaluation of optimized PCR and indirect ELISA for the detection of Morganella morganii in dairy cows - Zhang, Meihua; Li, Jiayi; Xue, Jianfeng; Xu, Huiling; Li, Muzi; Xia, Yibo; Qi, Changxi; Zhang, Pu; Liu, Yongxia; Liu, Jianzhu (Frontiers in Veterinary Science, 2025)
IntroductionMorganella morganii (M. morganii) is a Gram-negative opportunistic pathogen, whose increasing virulence and antibiotic resistance negatively impact dairy cow health and productivity, raising concerns in livestock health management. To mitigate this risk, rapid and reliable diagnostic methods for detection are essential. Currently, detection methods for M. morganii are underdeveloped, prompting us to develop both pathogenic and serological detection methods, including an optimized PCR technique and an indirect enzyme-linked immunosorbent assay (I-ELISA).MethodsThe optimized PCR method utilized bacterial suspensions directly as templates, bypassing the need for DNA extraction and thereby allowing the direct detection of M. morganii in fecal samples. Primer concentrations and annealing temperatures were optimized to minimize primer dimer formation, ensuring high specificity. Clinical evaluation was conducted using 771 fecal and nasal fluid samples collected from dairy farms in five regions. The I-ELISA method was developed using M. morganii lipoprotein (LPP) antigen. Parameters such as antigen coating, blocking conditions, and antibody dilution were optimized to improve specificity. Stability and reproducibility were validated through intra- and inter-assay tests. A total of 476 serum samples from dairy cows were tested to assess the method’s clinical applicability.ResultsThe optimized PCR method demonstrated high sensitivity and specificity, achieving a detection threshold of 0.2 CFU/μL. Clinical testing revealed a positivity rate of 1.4% among 771 fecal and nasal fluid samples. The I-ELISA method showed excellent stability and reproducibility, confirmed through intra- and inter-assay consistency. In testing 476 dairy cow serum samples, the positivity rate for M. morganii was 5.9%. These results indicate the utility of I-ELISA as a reliable serological diagnostic tool.DiscussionThe PCR and I-ELISA methods collectively offer practical solutions for the early clinical diagnosis of M. morganii infections in dairy cows. The PCR technique’s efficiency and sensitivity make it ideal for pathogen detection in fecal samples, while the I-ELISA method provides a robust platform for serological analysis. Together, these tools enable timely intervention, contributing to improved livestock health management and mitigating the negative impacts of M. morganii on dairy cow productivity. Future research may focus on further refining these techniques and exploring their applications in broader livestock management contexts.